KESENIAN RONGENG PASAMAN DI KENAGARIAN SIMPANG TONANG, KECAMATAN DUA KOTO, KABUPATEN PASAMAN (STUDI KASUS PERUBAHAN RONGGENG PASAMAN) - Gema Pratama; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Ronggeng Pasaman is a traditional art that is presented in the form of singing that is accompanied by music and dance. Dancer or players Ronggeng consists of four people, one of whom is a man who wears women's clothing and three others were wearing ordinary clothes and tidy. This study aims to determine the prior art in Kenagarian Ronggeng Pasaman Simpang Tonang, District Two Koto, to know Ronggeng Pasaman present in the District Tonang Kenagaian Simpang Dua Koto and to find out what factors cause changes Ronggeng Pasaman in Kenagaian Simpang sub-district Tonang two. The theory used in this study is the cultural theory and the theory of change. Culture consists of several patterns of real or hidden, of and for behavior acquired and transferred by symbols, which became decisive results of human groups, the main core of the culture is traditional notions (ie the obtained and have been historically), especially the values of belonging on the other hand as elements that affect the next action. Social change can be interpreted as changes that occur as a result of the mismatch of different elements in society, the change does not occur suddenly, but through various stages and processes of change.Keywords: Ronggeng Pasaman, Arts, Culture, Change